2010
DOI: 10.1038/cdd.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

Ciglitazone negatively regulates CXCL1 signaling through MITF to suppress melanoma growth

Abstract: We have previously demonstrated that the thiazolidinedione ciglitazone inhibited, independently of PPARc activation, melanoma cell growth. Further investigations now show that ciglitazone effects are mediated through the regulation of secreted factors. Q-PCR screening of several genes involved in melanoma biology reveals that ciglitazone inhibits expression of the CXCL1 chemokine gene. CXCL1 is overexpressed in melanoma and contributes to tumorigenicity. We show that ciglitazone induces a diminution of CXCL1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…Such a mechanism is supported by the clear evidence of complex heterodimeric interactions between chemokines, which lead to biological outcomes different from those of either of the individual component chemokines. [49][50][51] Similar to what happens in other systems, [52][53][54][55] our results showed that the CXCR2 signaling pathway played an important role in HSC maintenance. CXCR2 inhibition with the specific CXCR2 inhibitor SB225002 replicated the results for knockdown of CXCL4.…”
Section: Discussionsupporting
confidence: 78%
“…Such a mechanism is supported by the clear evidence of complex heterodimeric interactions between chemokines, which lead to biological outcomes different from those of either of the individual component chemokines. [49][50][51] Similar to what happens in other systems, [52][53][54][55] our results showed that the CXCR2 signaling pathway played an important role in HSC maintenance. CXCR2 inhibition with the specific CXCR2 inhibitor SB225002 replicated the results for knockdown of CXCL4.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, CXCR1 blockade inhibited the growth of human breast cancer stem cells (16). CXCL8 is not the only ELRþCXCL cytokine implicated in cancer progression as CXCL1 was shown to be important for the proliferation of esophageal (17) and melanoma cancer cells (18). CXCL7 is also implicated in the development of the lymphatic network through the regulation of VEGF-C and VEGF-D, two major growth factors for lymphatic endothelial cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…MCP-1 release levels were decreased by troglitazone in spite of the presence or absence of LPS. As for GROα, recent research showed that troglitazone and ciglitazone, but not pioglitazone, strongly decreased the TNF-α induced GROα, probably independently of peroxisome proliferator-activated receptor gamma agonist (Botton et al, 2011). Although the down-regulation of GROα shown in this study was due to some function of troglitazone, its role on hepatotoxicity remains unclear.…”
Section: Discussionmentioning
confidence: 45%